Institutional limits to land governance reform: Federal-state dynamics in Nigeria - Resnick, Danielle; Okumo, Austen (International Food Policy Research Institute, 2016)
Over the last decade, land governance has become a major priority for the development community.1 A particular focus has been on sub-Saharan Africa due to the recognized paradox of high levels of land availability and low productivity in the region (see Deininger et al. 2012). While poor land governance systems have long been identified as a key reason for this disjuncture, the relatively recent large-scale impetus to improve land governance emerged from the inclusion of land management in 2009 as one of the four pillars under the African Union’s Comprehensive Africa Agriculture Develop-ment Program (CAADP). Subsequently, in the wake of the G-8’s launch of the New Alliance for Food Security and Nutri-tion in 2012, many international initiatives have emerged to promote better land governance. These include the African Union’s Land Policy Initiative (AULPI) and the World Bank’s Land Governance Assessment Framework (LGAF). At the national level in Africa, land registration and land titling are the most common approaches to reform (Sikor and Müller 2009), with governments selecting among a broad spectrum of modalities to pilot. These include rural land use plans in some francophone countries (e.g., Benin, Burkina Faso, and Côte d’Ivoire), systematic land tenure regularization (Ethio-pia, Madagascar, Rwanda), and communal land demarcation and registration (e.g., Ghana, Mozambique, Tanzania) (see Byamugisha 2013).